Appraisal of the chelipeds size on Hepatus-pudibundus (Herbst, 1785) (Crustacea, Calappidae) in function of sex and maturation - Reigada, ALD; Negreirosfransozo, M. L.; Mantelatto, FLM (Inst Tecnologia Parana, 1994)
This paper appraises the influence of chelipeds on sexual and maturation phasis of the crab Hepatus pudibundus (Herbst, 1785), collected in Ubatuba (SP) region. The allometric constants obtained from the regression (carapace width X cheliped weight) adjusted to a power function (Y=aX(b)) were analysed. It was verified that males show larger chelipeds than females. The mean percentage of the chelipeds weight differs in sex and maturation.
Keywords: HEPATUS PUDIBUNDUS; CRAB; CHELIPEDS; BRACHYURA; CALAPPIDAE